Stress‐Release Functional Liquid Metal‐MXene Layers toward Dendrite‐Free Zinc Metal Anodes. Issue 16 (11th March 2022) - Gu, Jianan; Tao, Yi; Chen, Hao; Cao, Zhenjiang; Zhang, Yongzheng; Du, Zhiguo; Cui, Yanglansen; Yang, Shubin
Abstract: Zinc anodes are promising for zinc‐based batteries owing to the high theoretical capacity (820 mAh g −1 ), environmental‐friendliness, and good safety, but the uncontrollable dendrites greatly hamper their practical applications. Here, a special nonmodulus liquid GaIn electrode is designed to help understand the failure mechanism of Zn anodes, demonstrating that there is a huge crystalline stress in the plating Zn anode that causes the fast growth of substantial Zn dendrites. To solve this issue, a zinc‐enriched liquid metal (ZnGaIn) anode on flexible MXene layers (ZnGaIn//MXene) is fabricated, enabling efficient release of the stress in the plating Zn anode. Moreover, owing to the presence of zinc‐based liquid metal, the nucleation energy barrier is largely reduced and meanwhile the nucleation overpotential of Zn is reduced to 0 V versus Zn 2+ /Zn. Thus, the as‐prepared flexible zinc‐based anode delivers a long cycle life and high rate capabilities up to 8.0 mA cm −2 . As coupled with a MnO2 cathode, a full cell with ZnGaIn//MXene anode exhibits a stable and long lifespan, greatly benefiting the development of next‐generation zinc‐based batteries. Abstract : A special nonmodulus liquid GaIn electrode is designed to understand the failure mechanism of Zn anodes, demonstrating that there is a huge crystalline stress in the plating Zn anode, which causes the fast growth of substantial Zn dendrites. To solve this issue, a zinc‐enriched liquid metal (ZnGaIn) anode on flexible MXene layers (ZnGaIn//MXene) is fabricated, enabling efficient release of the stress in the plating Zn anode, leading to a stable cycle performance.